Self‐Assembled Peptide Nano‐Superstructure towards Enzyme Mimicking Hydrolysis. (23rd June 2021) - Chen, Yu; Yang, Yuqin; Orr, Asuka A.; Makam, Pandeeswar; Redko, Boris; Haimov, Elvira; Wang, Yannan; Shimon, Linda J. W.; Rencus‐Lazar, Sigal; Ju, Meiting; Tamamis, Phanourios; Dong, Hao; et al.
Abstract: The structural arrangement of amino acid residues in native enzymes underlies their remarkable catalytic properties, thus providing a notable point of reference for designing potent yet simple biomimetic catalysts. Herein, we describe a minimalistic approach to construct a dipeptide‐based nano‐superstructure with enzyme‐like activity. The self‐assembled biocatalyst comprises one peptide as a single building block, readily synthesized from histidine. Through coordination with zinc ion, the peptide self‐assembly procedure allows the formation of supramolecular β‐sheet ordered nanocrystals, which can be used as basic units to further construct higher‐order superstructure. As a result, remarkable hydrolysis activity and enduring stability are demonstrated. Our work exemplifies the use of a bioinspired supramolecular assembly approach to develop next‐generation biocatalysts for biotechnological applications. Abstract : The peptide nano‐superstructure employs a cyclic dipeptide as a building block, is inspired by the coffee roasting process, and can be easily synthesized. The self‐assembled biocatalyst displays enzyme‐like hydrolysis activity, with exceptional stability and recyclability. This catalytic peptide assembly provides a potent complement for minimalistic biocatalysts and offers an attractive alternative to the current arsenal of natural metalloenzymes.